Developing an effective IPE learning activity for midwifery and medical students: Use of a quality improvement model and researcher-teacher partnership methodology’ - Morgan, Sonya; Ormandy, Judy; Jackson, Christine; Honeyman, Lyndal; Spence, Rose; Maude, Robyn; McKinlay, Eileen (The Journal of Practice Teaching and Learning, 2025)
Background: There is little guidance available about how to develop effective interprofessional learning activities for midwifery and medical students to prepare them for future collaboration in the workplace. Purpose: This paper aims to describe how the use of a quality improvement methodology and researcher-teacher partnership approach improved an interprofessional education learning activity developed for pre-registration midwifery and medical students. Method: Employing a collaborative researcher-teacher approach, two iterations of the learning activity refined over two quality improvement cycles were undertaken. Mixed methods of data collection were used to assess each iteration. Modifications were made to the second iteration of the interprofessional education learning activity based on feedback from the first iteration. Discussion/Conclusions: Analysis of the second interprofessional learning activity modified according to feedback from the first iteration indicated improved learning outcomes. The study demonstrates the value of using a quality improvement methodology coupled with a researcher-teacher partnership to develop an effective interprofessional education learning activity for midwifery and medical students which has potential to increase workplace collaboration.